2020
DOI: 10.1021/acscatal.9b05496
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Tricationic Tris(1,2-diphenylethylenediamine) Cobalt(III) Hydrogen Bond Donor Catalysts with Defined Carbon/Metal Configurations; Matched/Mismatched Effects upon Enantioselectivities with Enantiomeric Chiral Counter Anions

Abstract: The enantiopure and diastereopure salts Λor Δ-[Co((S,S)-dpen) 3 ] 3+ 2Cl − BAr f − (Λ-or Δ-(S,S)-1 3+ 2Cl − BAr f − ; dpen/BAr f = 1,2-diphenylethylenediamine/B(3,5-C 6 H 3 (CF 3 ) 2 ) 4 ) and Λ-(S,S)-1 3+ 3Cl − are treated with salts of the enantiopure chiral monoanions (A − ) or dianions (A 2− ) 3-bromocamphor-8sulfonate (camphSO 3 − ), 1,1′-binaphthyl-2,2′-diyl phosphate (and three 3,3′-disubstituted derivatives), a related biphenanthryl species, tartrate, and Sb 2 (tart′− , and Λ-(S,S)-1 3+ 3A − are isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 75 publications
0
18
0
Order By: Relevance
“…In 2020, the same authors reported an interesting study involving the combination of the chiral [Co(( S,S )-dpen) 3 ] 3+ cations with chiral monoanions or dianions. 67 These diastereomeric salts could catalyze the addition of 1,3-dicarbonyl compounds to trans -β-nitrostyrene and di- tert -butylazodicarboxylate with significant variation in enantioselectivity, although the performances of the matched catalysts only occasionally exceeded those from their report in 2015. Recently, the same authors have also investigated a range of lipophilic [M(en) 3 ] n+ [BAr F 4 ] − salts with a variety of metal centers.…”
Section: Carbon–carbon Bond-forming Reactionsmentioning
confidence: 98%
“…In 2020, the same authors reported an interesting study involving the combination of the chiral [Co(( S,S )-dpen) 3 ] 3+ cations with chiral monoanions or dianions. 67 These diastereomeric salts could catalyze the addition of 1,3-dicarbonyl compounds to trans -β-nitrostyrene and di- tert -butylazodicarboxylate with significant variation in enantioselectivity, although the performances of the matched catalysts only occasionally exceeded those from their report in 2015. Recently, the same authors have also investigated a range of lipophilic [M(en) 3 ] n+ [BAr F 4 ] − salts with a variety of metal centers.…”
Section: Carbon–carbon Bond-forming Reactionsmentioning
confidence: 98%
“…2). 91,109,116,117,124,132,133,136 It was proven by single crystal X-ray crystallographic analysis that the counter anions formed multidentate hydrogen bonds with the amino groups of the cobalt(III) complexes. 155,156 Evidently, the Brønsted acidity of the NH 2 groups was enhanced significantly.…”
Section: 'Werner-type' Chiral Cobalt(iii) Complexes As Hydrogen Bond Donor Catalystsmentioning
confidence: 99%
“…2 'Werner-type' chiral octahedral cobalt(III) complexes as asymmetric hydrogen bond donor catalysts. 91,109,116,117,124,132,133,136 Scheme 1 Enantioselective Michael addition of dimethyl malonate to cyclopentenone catalysed by the chiral 'Werner-type' cobalt(III) complex D-1 (Gladysz, 2008). 91 The products were obtained with very high enantioselectivities (up to 499% ee) and excellent yields (up to 99%) (Scheme 3).…”
Section: 'Werner-type' Chiral Cobalt(iii) Complexes As Hydrogen Bond Donor Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…The absolute configuration of the cobalt metal centers is determined to be Λ based on the starting materials (R)-3, (S)-4, and the Flack parameter [0.015(5)] 12 obtained via the X-ray crystallographic analysis (Figure 2). 13 Recently, chiral cobalt(III) complexes have been recognized as highly enantioselective anionic catalysts 14 for Michael reaction, 15,16 halocyclization, 7,17 Mannich reaction, 18 and Povarov reaction. 19,20 We also carried out preliminary screening for the catalytic activity of the dimeric Λ-cobalt(III) complex 1 in the enantioselective bromocyclization of tryptamine derivative 6.…”
mentioning
confidence: 99%